Answer:
Step-by-step explanation:
G(-2) means "evaluate the equation at -2"; it's asking you to swap out the "x" in the equation and sub in -2.
g(x) = x² + 3x - 2 ... plug in -2
g(-2) = (-2)² + 3(-2) - 2 ... simplify
g(-2) = 4 + (-6) - 2 ... add/subtract
g(-2) = -4
(6 1/3) / (5/6) = (19/3) / (5/6) = 19/3 * 6/5 = 114/15 = 38/5
3 - 7^2 + 3 * 4^2
3 - 49 + 3 * 16
3 - 49 + 48
- 46 + 48
2
(7b - 2) / (-a + 1)....a = -2, b = 3, c = -1/3
where is he c in this equation ? Because if I just use a and b, my answer is not an answer choice
(7b - 10) / (a - 1)...a = -1, b = 5, c = -2/3
same as before...where is the c in this equation
V = (pi) r^2* h
V = (pi)(5^2)(7)
V = (pi)(25)(7)
V = 175(pi)
I believe the length is 18 and the width is 3.